Lincoln Cathedral
In detail, the Angle choir so called because of the angels carved between the arches of the triforium stage, exhibits a refinement of craftsmanship and structure which is most advanced. With its completion, the cathedral was perfectly adapted to the use of medieval worship, and it has hardly suffered any changes since.